Birth-weight, insulin levels, and HOMA-IR in new-borns at term - Narayanan, E.; Selvakumar, S.; Seeralar, A. T. Arasar (International Journal of Contemporary Pediatrics, 2017)
Background: Abnormal birth weight babies are prone to develop adverse metabolic and cardiovascular outcomes later in life. There is dearth of knowledge regarding correlation of birth-weight with hyperinsulinemia and insulin resistance in term newborns. Methods: Prospective cohort study was done in Institute of Obstetrics and Gynecology, Egmore, Madras Medical College from time period of May 2016 to November 2016. Inclusion criteria were newborns with gestational age between 38 to 41 weeks of normal pregnancies of healthy mothers aged 18 to 39 years. Incomplete/unclear data about mother’s health status, diabetes, history of gestational diabetes, hypertension, pre-eclampsia, eclampsia and conditions influencing glucose metabolism were exclusion criteria. In the first phase, cutoff point of HOMA-IR (homeostatic model assessment of insulin resistance) was established in 33 AGA neonates with birth-weight >2500 g and <4000 g. In the second phase, 34 term neonates were enrolled to determine whether LGA/SGA is related with hyperinsulinemia and elevated HOMA-IR. Serum insulin and serum glucose was obtained from cord blood. Hyperinsulinemia was defined by serum insulin levels ≥12.60 μU/mL and HOMA-IR ≥2.34. Multiple logistic regression analysis and Mann Whitney test was used to find association between birth-weight with hyperinsulinemia and HOMA-IR index. Results: A total of 67 newborns were enrolled; 24, 10, and 33 with SGA, LGA and AGA respectively. Hyperinsulinemia was more prevalent in 16 newborns particularly in SGA (p=0.01), whereas HOMA-IR was noted in 13 neonates (p=0.06). Multiple logistic regression analysis revealed LGA had a strong association with hyperinsulinemia (p=0.02) and HOMA-IR (p=0.02). Conclusions: Study revealed term LGA is associated with hyperinsulinemia and elevated HOMA-IR at birth.